Weak radiofrequency fields affect the insect circadian clock - Bartos, Premysl; Netusil, Radek; Slaby, Pavel; Dolezel, David; Ritz, Thorsten; Vacha, Martin (Journal of the Royal Society, Interface, 2019)
It is known that the circadian clock in Drosophila can be sensitive to static magnetic fields (MFs). Man-made radiofrequency (RF) electromagnetic fields have been shown to have effects on animal orientation responses at remarkably weak intensities in the nanotesla range. Here, we tested if weak broadband RF fields also affect the circadian rhythm of the German cockroach (Blatella germanica). We observed that static MFs slow down the cockroach clock rhythm under dim UV light, consistent with results on the Drosophila circadian clock. Remarkably, 300 times weaker RF fields likewise slowed down the cockroach clock in a near-zero static magnetic field. This demonstrates that the internal clock of organisms can be sensitive to weak RF fields, consequently opening the possibility of an influence of man-made RF fields on many clock-dependent events in living systems.
Keywords: Circadian Clocks; Radio Waves; cirkadiánní hodiny; Animals; Ectobiidae; Blattellidae; zvířata; rádiové vlny; Drosophila